2014
DOI: 10.1097/01.npr.0000454984.19413.28
|View full text |Cite
|
Sign up to set email alerts
|

Complementary and alternative treatments for primary dysmenorrhea in adolescents

Abstract: Primary dysmenorrhea is the most common gynecologic complaint among adolescents. Conventional treatments include nonsteroidal anti-inflammatory drugs and hormonal contraceptives, but complementary and alternative medicine is a growing area of interest. As patients seek such treatments, pediatric nurse practitioners should be aware of these options to offer the best advice to patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
21

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(52 citation statements)
references
References 35 publications
0
31
0
21
Order By: Relevance
“…Therefore, the second possibility to treat menstrual pain lies in the use of hormonal contraceptives, and combined oral contraceptives in particular. The aforementioned therapy combines estrogens and progestogens [57]. Combined hormonal contraceptives, including oral contraceptives, contraceptive rings, and patches act by limiting the growth of endometrium.…”
Section: Pharmacological Treatment Options For Menstrual Painmentioning
confidence: 99%
“…Therefore, the second possibility to treat menstrual pain lies in the use of hormonal contraceptives, and combined oral contraceptives in particular. The aforementioned therapy combines estrogens and progestogens [57]. Combined hormonal contraceptives, including oral contraceptives, contraceptive rings, and patches act by limiting the growth of endometrium.…”
Section: Pharmacological Treatment Options For Menstrual Painmentioning
confidence: 99%
“…Complementary medicine: Women should be encouraged to disclose the use of complementary medicine to ensure there are no interactions with concurrent medications. Most of the adult studies described involve small sample sizes (67). Studies have examined Vitamins B1, E, and D, Omega 3 fatty acids, magnesium and ginger with modest or no effect (11,67).…”
Section: Post-operative Considerationsmentioning
confidence: 99%
“…Most of the adult studies described involve small sample sizes (67). Studies have examined Vitamins B1, E, and D, Omega 3 fatty acids, magnesium and ginger with modest or no effect (11,67). A recent Cochrane review demonstrated limited effectiveness for fenugreek, fish oil, fish oil plus vitamin B1, ginger, valerian, Vitamin B1, sataria, and zinc sulfate (31).…”
Section: Post-operative Considerationsmentioning
confidence: 99%
“…Hormone therapy, such as gonadotropin-releasing hormone agonist (GnRHa) and the levonorgestrel-releasing intrauterine system (LNS-IUS), is widely used in the treatment of adenomyosis and endometriosis (5,6). However, the high recurrence rate, side effects and severe adverse events associated with these treatments lead patients to seek supportive complementary and alternative forms of medicine (CAM) (7).…”
Section: Introductionmentioning
confidence: 99%